(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Disasters pose significant challenges to healthcare systems worldwide, necessitating robust preparedness and response strategies. This abstract explores the pivotal role of medical administrators in disaster management, focusing on their responsibilities, challenges, and innovative approaches. Key components include risk assessment, emergency planning, resource allocation, communication, and training. Challenges such as limited resources and complex coordination are addressed, alongside case studies showcasing successful initiatives. Future directions emphasize leveraging technology and community engagement.